"Novum Testamentum editum est": The Five-Hundredth Anniversary of Erasmus's New Testament. Issue 1 (April 2016) - Elliott, J. K.
The 500th anniversary of Erasmus's Novum Instrumentum commemorates the first printed and published Greek New Testament in 1516. This article emphasizes that Erasmus's original motive for this publication was his new Latin version verifiable by his accompanying the translation by a Greek text. The latter was concocted from manuscripts he located in Basle; the article describes the manuscripts used. It also assesses the five editions of this bilingual text published in Erasmus's lifetime. A discussion covers the nature of his Latin compared to that of the Vulgate then currently in use and the opposition which his version caused. Later editions of the Greek New Testament are also described. An examination of the Comma Johanneum (1 John 5.7-8) is included.